Formula????o da estrat??gia competitiva pelo modelo de campos e armas da competi????o: verifica????o da validade para um fabricante de autope??as - Silva, Jair Francisco da (2009)
This work objective to verify if the formulation process of competitive business strategy and competitive operational strategy prescribed by the model field and weapons of the competition is capable to consider strategies that can generate competitive advantage to a company of the sector of auto parts. Although the model field and weapons of the competition to have been validated, the formulation process of competitive strategy for considered it still lacks of validation, therefore it was tested in few situations. The choice of this sector is justified, a time that the automotive sector has been the locomotive that has many decades comes hand spiking the economic growth of the country. The industry of auto parts, main supplier of the automakers, also has followed this growth and has searched strong to satisfy the necessities, requirements and yearnings of a market each more competitive time. For the gotten results, it can be concluded that the formulation process of competitive business strategy and competitive operational strategy prescribed by the model field and weapons of the competition generates competitive advantage for a company of the sector of auto parts. This process is based on the thesis of the model field and weapons of the competition: it company to be competitive, does not have more excellent condition of what to have high performance only in the weapons that give competitive advantage to it in the chosen field to compete in each pair product/market , thesis already previously validated.